IMPLEMENTASI PENGGUNAAN MEDIA GAMBAR DALAM MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS IV SD - Anggun Setiawan; Sumarno; Ida Dwijayanti (STKIP Subang, 2024)
This research aims to know the use of picturemedia to improve speaking sklills and to know the students speaking ability after using the picture media. The results of the study are as follows. First, by applying the picturemedia, it can improve students spakng skills. After the research was conducted, it looks that students can communicate in communicative, sort, and correct way. Second, by applying a picture media on the process of learning to improve students speaking skills, can be seen that there is an improvement on the score result on speaking skills, from 28 students, 82% (23 students) have got a score above minimum score, that is 75%.